Probing the molecular determinants of fluorinase specificity. Issue 17 (10th February 2017) - Yeo, W. L.; Chew, X.; Smith, D. J.; Chan, K. P.; Sun, H.; Zhao, H.; Lim, Y. H.; Ang, E. L.
Abstract : Probing the structural determinants of fluorinase enzyme specificity with 5′-chloro-5′-deoxyadenosine (5′-ClDA) analog substrates generated fluorinases with improved and novel activity. Abstract : Molecular determinants of FlA1 fluorinase specificity were probed using 5′-chloro-5′-deoxyadenosine (5′-ClDA) analogs as substrates and FlA1 active site mutants. Modifications at F213 or A279 residues are beneficial towards these modified substrates, including 5′-chloro-5′-deoxy-2-ethynyladenosine, ClDEA (>10-fold activity improvement), and conferred novel activity towards substrates not readily accepted by wild-type FlA1.